The Effect of Thursday Night Games on In-Game Injury Rates in the National Football League. Issue 8 (July 2020) - Perez, Jose R.; Burke, Jonathan; Zalikha, Abdul K.; Damodar, Dhanur; Geller, Joseph S.; Buskard, Andrew N.L.; Kaplan, Lee D.; Baraga, Michael G.
Background: Although claims of increased injury rates with Thursday night National Football League (NFL) games exist, a paucity of data exist substantiating these claims. Purpose: To evaluate the effect of rest between games on in-game injury rates as it pertains to overall injury incidence, location, and player position. Study Design: Descriptive epidemiologic study. Methods: Data were obtained from official NFL game books for regular season games from all 32 teams for the 2013-2016 seasons. All in-game injuries recorded in official game books were included. Rest periods between games were classified as short (4 days), regular (6-8 days), or long (≥10 days). Overall observed injury rates per team-game were analyzed in relation to different rest periods using negative binomial regression. For results with significant overall findings, pairwise comparisons were tested using the Wald chi-square test. Exploratory secondary analyses were performed in a similar fashion to assess differences in injury rates for the different rest periods when stratified by anatomic location and player position. Results: A total of 2846 injuries were identified throughout the 4 seasons. There was an overall significant difference in injuries per team-game between short, regular, and long rest ( P = .01). With short rest, an observed mean of 1.26 injuries per game (95% CI, 1.06-1.49) was significantly different from the 1.53 observed injuries per game with regular rest (95% CI, 1.46-1.60; P = .03), but not compared with the 1.34 observed injuries per game with long rest ( P = .56). For player position, only the tight end, linebacker, and fullback group demonstrated significant differences between the injury rates for different rest categories. Quarterback was the only position with more injuries during games played on Thursday compared with both regular and long rest. This specific analysis was underpowered and the difference was not significant ( P = .08). No differences were found regarding injury rates in correlation with differences in rest periods with different injury locations. Conclusion: A short rest period between games is not associated with increased rates of observed injuries reported in NFL game books; rather, our data suggest there are significantly fewer injuries for Thursday night games compared with games played on regular rest. Future research correlating rest and quarterback injury rates is warranted.